Molecular biological correlation of fluorine-18 fluorodeoxyglucose uptake in esophageal squamous cell carcinoma. Issue 10 (October 2016) - Hirose, Yasumitsu; Kaida, Hayato; Kawahara, Akihiko; Matono, Satoru; Tanaka, Toshiaki; Kurata, Seiji; Kage, Masayoshi; Ishibashi, Masatoshi; Abe, Toshi
Abstract : Objective: The aim of this study was to assess the relationship between fluorine-18 fluorodeoxyglucose ( 18 F-FDG) uptake and molecular biological markers in esophageal squamous cell carcinoma (ESCC) patients. Methods: Our patient population included 51 patients who underwent 18 F-FDG PET/computed tomography before surgery. Excised tumor tissue was analyzed immunohistochemically using monoclonal antibodies for glucose transporter-1 (GLUT-1), GLUT-3, CD34 [microvessel density (MVD) marker], CD68 (macrophage marker), and CD163 (tumor-associated macrophage marker). The relationships among pathological factors [pathological T stage (p-T stage), pathological lymph node status (p-N status), pathological stage (p-stage), and pathological tumor length], the maximum standardized uptake value (SUVmax ), and these molecular biological markers were evaluated using Spearman's rank test and the Kruskal–Wallis test. Results: GLUT-1, GLUT-3, CD34, and CD163 significantly correlated with SUVmax ( r =0.547, P <0.001 for GLUT-1; r =0.569, P <0.001 for GLUT-3; r =0.463, P =0.001 for CD34, r =0.455, P =0.001 for CD163), whereas SUVmax, GLUT-1, GLUT-3, CD34, and CD163 significantly correlated with p-T stage ( r =0.552, P <0.001 for SUVmax, r =0.307, P =0.03 for GLUT-1, r =0.349, P =0.013 for GLUT-3, r =0.313, P =0.027 for CD34, r =0.526 for CD163, P <0.001), but not with p-N status. CD68 levels showed no significant correlation with SUVmax, p-T stage, p-stage, or p-N status. Conclusion: SUVmax, GLUT-1 expression, GLUT-3 expression, MVD, and TAMs show a relationship with the tumor stage and extent of ESCC. GLUT-1, GLUT-3, MVD, and TAMs are associated with the mechanism of 18 F-FDG uptake in ESCC.